THE EFFECT OF THE RETURNS OF GLOBAL STOCK INDEXES AND GLOBAL COMMODITIES TOWARD IHSG RETURNS PERIOD 2009 â 2018 - Tyas Raharja, Rahmanto
The Government of Indonesia through Indonesia Stock Exchange’s “Yuk Nabung Saham” national campaign has the purpose of increasing the number of new investors, especially youth, in Indonesia. The campaign persuades people to invest in stock market because of the potential return offered by investing in stock market, supported by the strong economic indicators of Indonesia. In the first semester of 2018, the global stock markets, including Indonesia Stock Market, experienced high volatility with the tendency of weakening that affects the return that investors get. A lot of investors shocked and there are a lot of speculations and news spread among investor about the reasoning and impact of the global stock indices. The results of similar studies show that there is linkage between global markets, either stock market or commodities market, where movement in one market in the global can affect other countries’ stock market movement. A need therefore arises to investigate the relationship between the global markets toward Indonesia Stock Market (IHSG), where the researcher chose to research the relationship between four global stock indexes those are DJIA (United States of America), NIKKEI 225 (Japan), Hang Seng (Hongkong), and STI (Singapore) and three commodities market (crude oil, coal, and gold) towards the returns of IHSG. Researcher built two models, where the second model data is derived by making equal weighted index from the selected global stock indexes and global commodities. The data used in this research is the returns of each variable derived from the monthly closing price from secondary data of each variable. By using multiple linear regression method, this research found that simultaneously, the returns of global stock indexes and commodities have significant effect toward IHSG returns in both model. While partially, the returns of DJIA, STI, and Crude Oil significantly affect returns of IHSG, while the returns of NIKKEI, Hand Seng, Coal, and Gold has no significant effect partially to the IHSG return. The research also found that the returns of NIKKEI, Hang Seng, and Crude Oil have negative effect to the IHSG returns while the returns of DJIA, STI, Coal, and Gold have positive effect to the IHSG returns within period of 2009-2018. The second model of the research also found that partially, the returns of global stock indexes has significant effect to the return of IHSG, while the returns of global commodities has no significant effect partially to the returns of IHSG. The first model is able to explain returns of IHSG better than the second model. Therefore, the implication of this study is that we can take into account the returns of global stock indexes and global commodities as consideration to predict the return of IHSG.